2018
DOI: 10.32879/pjpbs.2017.3.2.175-187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motivation Behind Volunteerism on Satisfaction with Life among University Students

Abstract: Volunteering is any action in which time is offered wholeheartedly to give advantage to other persons, assembling or cause. Purposive sampling technique was applied for collecting information. The sample of this study consisted of students (N=184) including male (n =83) and female (n=101) students of different universities of Karachi. Besides demographic sheet two instruments were used they included Volunteer functions inventory and satisfaction with life scale for data collection from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Wiepking et al (2023) indicated that males and females approach voluntary work in different ways. This is in line with a study by Emad et al (2018) that revealed male and female university students differ significantly in the factors that drive their involvement. Hallmann (2015) as well discovered that females have distinct motivations for volunteering than males, which reflects their involvement in sports volunteering.…”
Section: Volunteers' Motivation Based On Gendersupporting
confidence: 92%
“…Wiepking et al (2023) indicated that males and females approach voluntary work in different ways. This is in line with a study by Emad et al (2018) that revealed male and female university students differ significantly in the factors that drive their involvement. Hallmann (2015) as well discovered that females have distinct motivations for volunteering than males, which reflects their involvement in sports volunteering.…”
Section: Volunteers' Motivation Based On Gendersupporting
confidence: 92%
“…Why could not volunteer activity be the best reference and entrance ticket to the competitive sector when the market is ready to open and restart? In addition, volunteering provides a shielding effect on the volunteers from being isolated in hard times [55]. To achieve this, even a non-profit organization should be ready to accept a new way of time giving.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gender comparison, gender differences have also been broadly studied [12,[54][55][56]. Some results indicated that job satisfaction was related to volunteerism among female employees, but not among male employees [57].…”
Section: Personal Characteristicsmentioning
confidence: 99%